Computed tomography measured tissue density of pectoral muscle and liver predicts outcomes in heart transplant recipients. Issue 2 (26th May 2022) - Kuchnia, Adam J; Lortie, Jevin; Osterbauer, Katie; Hess, Timothy; Stabo, Nicholas; Tsuchiya, Nanae; Wheeler, Nathan; Binkley, Neil; Francois, Christopher; Schiebler, Mark; Hermsen, Joshua; Dhingra, Ravi
Abstract: Background: Computed tomography (CT)‐derived measures of tissue quality can add to frailty assessment and improve selection of candidates for heart transplant. We investigated the prognostic value of CT measures of tissue density for predicting hospital length of stay (LOS) and mortality post‐transplant. Methods: All patients at a quaternary care hospital between 1999 to 2018 with preheart transplant CT scans and available data on transplant outcomes were eligible ( n = 189), including a subset within the total cohort with scans 6‐month pretransplant ( n = 103). Axial chest CT scans were analysed for liver and muscle density at the 12th thoracic vertebrae and aortic arch landmarks, respectively. Cox and linear regression models examined the risk of death and LOS, respectively, according to median (above or below) pectoral muscle density. Low‐density muscle (LDM) area and liver density were analysed as continuous variables. Results: Out of 157 patients with readable CT scans (median age 55 years, interquartile range [50–60] 10% women), 31 died on 1‐year follow up. Patients with higher than and at median pectoral muscle density (39.5 Hounsfield Unit [HU]) had better 1‐year survival in the overall cohort (hazard ratio [HR] 0.82, 95% confidence interval [CI] 0.673, 0.989; p = 0.039), with the 6‐month cohort showing a trend (HR 0.79, 95% CI 0.603, 1.023; p = 0.074) towards improved survival. Conversely, every 5‐cm 2 increase in pectoral LDM area was associated with 2.4‐day lower LOS ( p = 0.045) in the overall cohort, and a 2.6‐day lower LOS in the 6‐month cohort ( p = 0.05). Patients with higher ratio of normal‐density muscle to LDM had higher LOS ( p < 0.01). Every 5‐HU increase in liver density at a region of interest was associated with 0.24‐day higher post‐transplant LOS in the overall cohort, and a 0.41 higher LOS in the 6‐month cohort ( p ≤ 0.05). Conclusions: Patients with higher preheart transplant pectoral muscle density had greater 1‐year survival. Higher pectoral LDM area was associated with decreased LOS post‐transplant and higher liver density was associated with increased LOS. These findings raise possibilities that measures of muscle density as they reflect to quality of muscle may have prognostic implications. Future studies with prospective design are needed to confirm these findings.